Transition-metal-free intramolecular double hydrofunctionalization of alkyne to access 6/7/5-fused heterocyclic skeletons - Aghaie, Kimia; Amiri, Kamran; Rezaei-Gohar, Mohammad; Rominger, Frank; Dar’in, Dmitry; Sapegin, Alexander; Balalaie, Saeed (Chemical communications, 2024)
We describe a novel intramolecular double hydrofunctionalization cyclization of alkyne with nitrogen and oxygen nucleophilic groups to construct valuable 6/7/5-fused heterocyclic products. This post-Groebke-Blackburn-Bienaymé (GBB) reaction introduces a new class of functionalized isocyanides. Transition-metal-free cyclization, broad substrate scope, and high atom economy were some features of the present protocol.
Zuerst veröffentlicht: 7. Februar 2024
Gesehen am 06.06.2024